Pragmatic guide to peripheral nerve disease and the role of clinical biomarkers. Issue 6 (18th July 2022) - Keh, Ryan Yann Shern; Shah, Sachit; Lilleker, James B; Lavin, Tim; Morrow, Jasper; Carr, Aisling S; Lunn, Michael P
Abstract : In clinical neurology practice, there are few sensitive, specific and responsive serological biomarkers reflecting pathological processes affecting the peripheral nervous system. Instead, we rely on surrogate multimodality biomarkers for diagnosis and management. Correct use and interpretation of the available tests is essential to ensure that appropriate treatments are used and adjusted in a timely fashion. The incorrect application or interpretation of biomarkers can result in misdiagnosis and delays in appropriate treatment. Here, we discuss the uses and limitations of such biomarkers and discuss possible future developments.